HERMENEUTIKA MUHAMMAD SYAHRUR ( KATA NISA’ DALAM QS. ALI IMRAN:14 ): (KAJIAN HERMENEUTIKA MUHAMMAD SYAHRUR) - Dwi Elok Fardah; Maula Sari (Sekolah Tinggi Agama Islam Sadra, 2022)
One of the Islamic religious thinkers who has contributed to the contemporary era is Muhammad Syahrur. Syahrur argues that in understanding the verse, it is not always fixed on traditional interpretation. On Q.S Āli ‘Imrān [3]: 14 in interpreting the word nisā’ which according to him, the word if it is interpreted as